SIRT1 in Secretory Organ Cancer - Frazzi, Raffaele (Frontiers in Endocrinology, 2018)
Mammalian silent information regulator 1 (SIRT1) has been reported to play a role in cancers of the secretory organs including thyroid, pancreatic endocrine tumors and ovary [1-4]. A recent meta-analysis conducted on 37 selected studies on human cancers analyzes the correlations of overall survival (OS), disease-free survival (DFS) or relapse-free survival (RFS) with SIRT1 expression [5]. Interestingly, SIRT1 overexpression associates to a worse OS in liver and lung cancers, while is not correlated to OS in breast cancer, colorectal and gastric carcinoma. Collectively, the meta-analysis evidences as an unfavourable OS associates to SIRT1 expression for solid malignancies. Interestingly, a consistent result has been recently reported also for diffuse large-B cell lymphoma and follicular lymphoma, the two major subtypes of Non-Hodgkin lymphomas [6]. Given the growing importance of this class of lysine/histone deacetylase in human endocrine malignancies, a rational and focused literature assessment is desirable in light of future clinical translations.